2017
DOI: 10.4174/astr.2017.92.4.184
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting outcomes of laparoscopic Nissen fundoplication for gastroesophageal reflux disease: experience at a single institution in Korea

Abstract: PurposeLaparoscopic fundoplication is considered the standard surgical treatment for gastroesophageal reflux disease (GERD) in Western countries. However, some patients experience poor surgical outcomes with this procedure. The study aimed to identify the predictive factors of the surgical outcomes of laparoscopic Nissen fundoplication for the treatment of Korean GERD patients.MethodsSixty-one patients with GERD were treated using laparoscopic Nissen fundoplication between November 2012 and February 2015. Symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…Although the number of operations is much less than the number of operations in the Western countries, there have been several reports on the outcomes of anti-reflux surgery in Korea. [2][3][4][5] The Korean anti-reflux surgery study group (KARS) conducted a nationwide survey among surgeons in Korea and reported the outcome of anti-reflux surgery in 87 patients. The results reported that laparoscopic fundoplication is an efficient treatment method for controlling GERD symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the number of operations is much less than the number of operations in the Western countries, there have been several reports on the outcomes of anti-reflux surgery in Korea. [2][3][4][5] The Korean anti-reflux surgery study group (KARS) conducted a nationwide survey among surgeons in Korea and reported the outcome of anti-reflux surgery in 87 patients. The results reported that laparoscopic fundoplication is an efficient treatment method for controlling GERD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…All previous reports in Korea were of a retrospective case series nature. [2][3][4][5] There has been no prospective study to date. The present study was the first multicenter prospective study evaluating the outcome of laparoscopic anti-reflux surgery in Korea.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations